The Shadow of Neo-Hanbalism: The Idea of Islamic Extremism in Indonesia - Hasyim, Syafiq (Islamic Studies Review, 2022)
This article seeks to explore how Neo-Hanbali approaches to Islam have played a key role in instigating Islamic extremism in Indonesia. Neo-Hanbali refers to those who identify themselves as the followers of Ibn Hanbal and his students, such as Ibn Taymiyyah, Ibn Qayyim al-Jawziyyah, and Muḥammad ibn ʿAbd al-Wahhāb. Many Indonesian Islamic extremist groups argue that their struggle is driven by their desire to implement a purer form of Islam and that the thinking of Ibn Hanbal and Neo-Hanbali scholars provide the justification for this goal. To begin with, this article outlines the emergence of Ibn Hanbal’s thought and Neo-Hanbalism in the Indonesian Muslim community in general and Salafi groups in particular. The article particularly discusses: first, the discursive acceptance of Ibn Ḥanbal’s students in Indonesia and their ties to Islamic extremism; second, the links between Ibn Hanbal’s disciples on the one hand and Salafi and Wahhabi groups and movements on the other hand in the context of Islamic extremism; third, the connection between the concepts of tajdid (Islamic renewal) and takfir (excommunication) in Indonesia. This article attempts to understand Neo-Hanbali thought from a non-monolithic perspective in Indonesia. In this regard, it examines the acceptance of Neo-Hanbali ideas among social and political organisations in Indonesia. Finally, this article discusses Neo-Hanbalism in the context of the future development of political Islam in Indonesia to better understand whether these groups will be able to adapt to the changing political situation in Indonesia, or whether they will remain committed to Islamic extremism.